Mobile IP technology and applications - Raab, Stefan 1966- (Cisco Press, 2005)
Real-world solutions for Cisco IOS® Mobile IP configuration, troubleshooting, and management First book to address the practical application of Mobile IP in real-world environments Detailed case studies show how to apply Mobile IP in real-world networksConfiguration examples demonstrate working implementations of the Cisco Mobile IP components Includes troubleshooting methodologies for common failures and best practices The Internet and mobile communications are defining how and when people access information, with cellular phones, PDAs, and laptops driving the need for ""always-on"" I.
Includes bibliographical references and index. - Print version record
Keywords: Computer network protocols; Wireless Internet; Mobile communication systems; TCP/IP (Computer network protocol); Protocoles de réseaux d'ordinateurs; Internet mobile; Radiocommunications mobiles; TCP/IP (Protocole de réseaux d'ordinateurs); Electrical & Computer Engineering; Engineering & Applied Sciences; Electrical Engineering; Electronic resource